IMPROVING SKILLS OF CANDIDATE TEACHERS OF CHILDREN WITH VISUAL IMPAIRMENT AS SIGHTED GUIDE - Rudiyati, Sari (Dewantara, 2014)
This study aims to improve the skills of candidate teachers of children with visual impairment as a sighted guide/companionfor blind peoplethrough training and mentoring. The subjects of this study were the students of the Department of Special Education of Faculty Education Yogyakarta State University that takes concentration education of children with visual impairment.Data analysis using descriptive analysis. The results showed that the training and mentoring is proven to improve skills of candidate teachers ofchildren with visual impairmentas a sighted guide/companion for blind people have done with two cycles of action. Results cycle 1 of actions undertaken by the practice as a sighted guide/companion for blind people accompanied by a pre-test as a baseline, seven candidate teachers of children with visual impairment cumulatively reached an average score of 2.47 and a post-test achieving an average score of 3.24; 31.17% have been able to improve the skills of the sevencandidate teachers of children with visual impairment as a sighted guide/companion for blind people. The results of the actions undertaken by cycle 2 had done with exercises and mentoring as a sighted guide/companion to look out for blind people , the seventh candidates teacher of children with visual impairment cumulatively reached an average score of 3.24 increased 29.63% to an average score of 4.2 with a good rating and has exceeded the target minimum standard score/weight percentage value of 3.5 or better stated, reaching 76%, but has not reached the predicate is very good because it has not reached a score of> 4.2 to 5.0 or 86% -100%, so it has reached the target action and not there needs to be action cycle 3.